Uncertainties in the measurement of the atmospheric velocity due to balloon-gondola pendulum-like motions - Alexander, Pedro Manfredo (2011)
Balloons lead to the highest vertical resolution of air velocity data actually attainable from atmospheric soundings. However, the pendulum-like motion of the balloon-gondola system may significantly affect these measurements if the distance between balloon and gondola is large. This may prevent the study of the highest vertical resolution range obtained. Also, if not appropriately discriminated, these fluctuations could be confused with small scale or turbulent oscillations of the atmosphere. It is shown from simple energy considerations that horizontal and vertical wind velocity perturbations introduced in the observations by the pendulum motion may usually be comparable to typical measurements. Vertical velocity data that were obtained with an instrumented gondola in a zero pressure balloon, which typically reach the lower stratosphere, are analyzed and found to be in agreement with the above statements. The pendulum-like behavior in this sounding seems to be stimulated by the buoyant oscillation of the atmosphere. © 2010 COSPAR. Published by Elsevier Ltd. All rights reserved.